2010
DOI: 10.1186/1471-2393-10-62
|View full text |Cite
|
Sign up to set email alerts
|

The utility of clinical care pathways in determining perinatal outcomes for women with one previous caesarean section; a retrospective service evaluation

Abstract: BackgroundThe rising rates of primary caesarean section have resulted in a larger obstetric population with scarred uteri. Subsequent pregnancies in these women are risk-prone and may complicate. Besides ensuring standardised management, care pathways could be used to evaluate for perinatal outcomes in these high risk pregnancies. We aim to demonstrate the use of a care pathway for vaginal birth after caesarean section as a service evaluation tool to determine perinatal outcomes.MethodsA retrospective service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…These findings are in agreement with some studies [28,29,33,37], but disagree with others [6,32] that demonstrated a higher rate of adverse neonatal outcome in association with a failed trial of scar, non-availability of modern neonatology equipment, or increased uterine rupture rate.…”
Section: Commentssupporting
confidence: 38%
“…These findings are in agreement with some studies [28,29,33,37], but disagree with others [6,32] that demonstrated a higher rate of adverse neonatal outcome in association with a failed trial of scar, non-availability of modern neonatology equipment, or increased uterine rupture rate.…”
Section: Commentssupporting
confidence: 38%
“…With our restrictions on VBAC, we recorded fewer vaginal deliveries, but also less uterine rupture / dehiscence, as was found in rural Zimbabwe [Spaans et al, 1997]. In settings where such cautions were not applied, higher morbidity levels were observed , Adanu & McCarthy, 2007Olusanya & Solanke, 2009;Sepou et al, 2003;Nwokoro et al 2003;Oboro et al, 2010;Wanyonyi & Karuga, 2010]. A large multicenter propective study in a western country with a uniform and well organised delivery care system emphasized the greater perinatal risk associated with a trial of labor [Landon et al, 2004].…”
Section: Previous Cesarean Deliverymentioning
confidence: 99%
“…It is possible that this conservative approach favoring repeat cesarean procedures has emerged owing to human and physical resource constraints that limit the ability either to monitor both maternal and fetal well‐being closely, or to facilitate an emergency surgical response should uterine rupture or fetal compromise occur. However, more research is needed to understand decision making among providers because the TOL rate in the present study was lower than that reported in other settings where resource constraints are likely to be similar …”
Section: Discussionmentioning
confidence: 58%